School Principal Leadership Strategies in Enhancing Teacher Profesionalism Through Strengthening Digital Competencies at SMPN 1 and SMPN 3 Tualang - Rini, Rini; Lestari, Slamet (Journal of Educational Sciences, 2025)
This study aims to 1) analyze the leadership strategies of school principals, 2) the programs designed and implemented by school principals, and 3) the aspects that support and hinder school principals' leadership in improving teacher professionalism through strengthening digital competencies at SMPN 1 and SMPN 3 Tualang. This study uses a qualitative research method. The subjects of this study were principals, teachers, and school operators at SMPN 1 and SMPN 3 Tualang. The results showed that: (1) the principal of SMPN 1 Tualang applied a supportive approach that encouraged collaboration among teachers, while the principal of SMPN 3 Tualang emphasized an administrative approach; (2) the teacher digital competency development program at SMPN 1 Tualang is implemented through training and workshops, while at SMPN 3 Tualang, despite efforts to provide technological assistance, limited facilities and a lack of ongoing technical support limit the effectiveness of technology implementation in learning; and (3) the main challenge at SMPN 1 Tualang is the digital skills gap among teachers, especially senior teachers who feel pressured to master technology, while at SMPN 3 Tualang, an additional challenge is the high administrative burden, which limits teachers' time and energy to participate in training programs.